Reutilização de resíduos sólidos em uma Comunidade isolada no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This research is constituted in a Case Study in Village Paricatuba, located near the city of Manaus in Amazonas State. Its overall objective to apply the use of biodecomposer as an alternative to the reuse of household organic waste in isolated community and as specific Set the community and the number of families to be affected by the project; Diagnosing the socioeconomic situation of families involved in the project; Develop an appropriate biodecomposer the region; Analyze the results occurred in the community since the introduction of biodecomposer. The theoretical seek refuge in the dialectic divided into 3 parts. The first deals with composting, the second on the management of solid waste and the third on environmental education, recognize three dimensions to analyze, develop or change the waste management: a) stakeholders; b) the elements or phases of the movement or flow of materials; c) the final disposition. Research has analytical and theoretical procedure is qualitative document. And as preliminary results it was verified to decrease organic waste discarded in the environment, changes in habits and behavior on the part of those involved in the project. And on the other hand the use of organic fertilizer and bio-fertilizer generated by biodecomposer.
Keywords: Educação ambiental; Biodecompositor; Reaproveitamento; Resíduos orgânicos sólidos; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO